The Beats’ Identification with the Marginalized Groups as a Means of Decentralization - Neyshaburi, Ehsan Emami (International Journal of Language and Literary Studies, 2020)
Because the cold war had already started and atomic annihilation was impending, America was panicked into bringing about homogeneity and centralization. The government thought that diminution of heterogeneity and propagation of the privileged discourses could guarantee the country against the threat. Opposing this, the Beats strived to bring about difference and heterogeneity to guarantee their society against tastelessness and lack of individuality, as the inevitable corollaries of this policy. They identified themselves with the marginalized groups because they knew that being on the periphery of American society, these groups had not been corrupted by capitalism. Their purity, difference from the rest, and natural condition helped the Beats fulfil their purpose. Some critics believe they were insensitive to the plight of those groups and only misused them and some others say that the Beats had an ambivalent attitude towards them and the positive and negative aspects of their relation should be considered. This paper is going to support the second view.